Keabsahan Perjanjian Lisan Dalam Masyarakat Adat - Sopamena, Ronald Fadly; Fadillah, Astuti Nur; Sopamena, Siska Vilonia Indah; Rumahlewang, Fruli; Sahupala, Gregory Anthonio (Faculty of Law, Universitas Pattimura, 2023)
Introduction: An agreement is a legal action that is often carried out by the community in order to fulfill the necessities of life. This is also often practiced by indigenous peoples in their daily lives.Purposes of the Research: This writing intends to examine the validity of the agreements practiced in indigenous peoplesMethods of the Research: This writing uses a normative juridical method based on primary and secondary legal materials, namely research that refers to the norms contained in laws and regulations.Results of the Research: The validity of an agreement is determined by whether or not the agreement is fulfilled with the legal terms of the agreement specified in Article 1320 of the Civil Code. Based on the author's analysis, agreements made in indigenous peoples fulfill the legal requirements of an agreement so that even if they are only made orally, they still have legal consequences.